The 1950s in the Zabrana Family: The Diary as a Space of Reflexivity - Spevacek, Jan (Bohemica Olomucensia, 2025)
This study examines literary and personal reflections on the period of the 1950s in the Zabrana family, focusing on three key texts: Ohlednuti (1994) by Jirina Zabranova, Cely zivot (1992) by Jan Zabrana, and Flashky (2014) by Eva Zabranova. These works offer a unique opportunity to look at the same decade through the eyes of three generations. Based on Philippe Lejeune's concept of the diary as ``anti-fiction'', Jan Patocka's concept of reflexivity, and Paul Ricoeur's triple mimesis, this study outlines how each of the texts mentioned transforms personal experience into a testimony of time. Jirina Zabranova's memoir documents the brutal realities of a political prisoner, Jan Zabrana's diary captures existential disillusionment and historical despair of Czech poet and translator, while Eva Zabranova's Flashky reflect the lingering effects of the past on family relationships. The study contributes to broader discussions on autobiographical writing, memory studies, and the role of literature in preserving historical experience.
Keywords: Jan Zabrana; diary; family memory; reflexivity; life writing; 1950s in Czechoslovakia